If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(6x + 11) = 35 Reorder the terms: x(11 + 6x) = 35 (11 * x + 6x * x) = 35 (11x + 6x2) = 35 Solving 11x + 6x2 = 35 Solving for variable 'x'. Reorder the terms: -35 + 11x + 6x2 = 35 + -35 Combine like terms: 35 + -35 = 0 -35 + 11x + 6x2 = 0 Factor a trinomial. (-7 + -2x)(5 + -3x) = 0Subproblem 1
Set the factor '(-7 + -2x)' equal to zero and attempt to solve: Simplifying -7 + -2x = 0 Solving -7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5Subproblem 2
Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667Solution
x = {-3.5, 1.666666667}
| (2x^2-3)(5x^3-6)= | | 3k^3*t-2x^2=t | | 3/4-3/5x=9/20 | | 2800=p*.04*3.5 | | 11z-5-7z=7 | | -2-10=t/10 | | 2(3-4x)=6-7(2x+4) | | 12y+4y=144y | | 4b^2=64 | | 5x+4y=242 | | 20*3= | | 3x+13=25 | | 9-8x= | | -12=2+5n+2v | | (0.4a-0.1)(0.07a+1)=0 | | 16y+2(2y+3)=16 | | 6y-8y-3=10 | | 2b-5-5b-9= | | X-.0275X=80.25 | | 0.2b+5=0.5b+14 | | 5x+xy=y | | (6-4)x49/7 | | X-.0275*X=97.25 | | 5x+12=-2x(-7)+12 | | (x^2)-(20x)+1=0 | | 25/40=60/x | | -3(4-(3b+3))=6-3(3b+8) | | 5x+15=8x-6 | | 8-(6-8x)=4x+13 | | 0.05(8-x)+0.1x=0.64 | | 5x-34=0 | | 8(2x+3)=72 |